The Effectiveness of Using the Siskeudes Application in Village Financial Accountability in Posiga and South Bolaang Mongondow Districts - Arifin Tahir; William Mooduto; Raston Mooduto (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The research objectives are as follows; 1) To find out and analyze the effectiveness of using the siskeudes application in village financial accountability in Posigadan, South Bolaang Mongondow Districts; 2) to find out and analyze the factors that influence the effectiveness of using the siskeudes application in village financial accountability in Posigadan, South Bolaang Mongondow Districts. The research was conducted using a qualitative approach. The type of research used in this thesis research is qualitative descriptive research. In this descriptive study the author uses a case study pattern or case study. The results show that: 1) the effectiveness of using the siskeudes application in village financial accountability in Posigadan, South Bolaang Mongondow Districts has been running but is not optimal. To see the effectiveness of the use of Siskeudes, it can be seen from several indicators: a) the understanding of village officials in implementing Siskeudes still needs to be improved: b) the implementation of the Village Financial System (Siskeudes) application in Posigadan District has been said to be successful because it has been right on target: c) punctuality that financial reporting through the application of the village financial system has been in accordance with the specified time; d) the use of the village financial system application, the objectives to be achieved can be met. The village financial system application report (Siskeudes) produces reports that are easy to understand and in accordance with the existing format so that it really helps the village government in better financial management, especially in improving village financial transparency; 2) What are the factors that influence the effectiveness of using the siskeudes application in village financial accountability in Posigadan, South Bolaang Mongondow Districts, namely human resources, facilities and infrastructure.